Effects of different training methods on open-skill and closed-skill agility in basketball players: A systematic review and meta-analysis - Zhang, M.; Li, F.; Jiao, J.; Liang, W.; Gomez, M.-A.; Scanlan, A. T. (Sports Medicine - Open, 2025)
Background Open-skill and closed-skill agility attributes are pivotal for achieving success in basketball. However, systematic synthesis of evidence regarding the effectiveness of different basketball-specific training methods on agility performance is lacking among basketball players in the literature. Consequently, this systematic review with meta-analysis aimed to evaluate the effectiveness of prominent training methods in improving open-skill and closed-skill agility in basketball players.